ANALISIS PENGARUH KECUKUPAN MODAL, EFISIENSI, LIKUIDITAS, NPL, DAN PPAP TERHADAP ROA BANK - Krisna Hidajat (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This research is performed in order to test the influence of the variable, Capital Adequacy Ratio (CAR), Biaya Operasi terhadap Pendapatan Operasi (BOPO), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Pembentukan Penyisihan Aktiva Produktif (PPAP) toward Return on Asset (ROA).Methodology reseach as the sample used sensus. Sample was accuired 23 banking company listed in JSX over period 2010-2013. Data analysis with multi linear regression of ordinary least square and hypotheses test used t-statistic dan F-statistic at level of significance 5%, a classic assumption examination which consist of data normality test, multicolinierity test, heteroskedasticity test and autocorrelation test is also being done to test the hypotheses.During research period show' as variable and data research was normal distributed. Based on multicolinierity test, heteroskedasticity test and autocorrelation test classic assumption deviation has not founded, tihis indicate that the available data has fulfill the condition to use multi linear regression model. Empirical evidence show as CAR. BOPO and LDR toward ROA banking listed in JSX over period 2010-2013 at level of significance less than 5% (as 0,01%,0,01% and 0,6% each). While, two independent variable NPL, and PPAP not influence toward R0A at level of significance more than 5% at 88,2% and 72,7%. Where it was proved that together this research is performed in order to test the influence of the variable CAR, BOPO, LDR, NPL and PPAP to have influence toward banking ROA in JSX at level less than 5% (with level of significance 0,05). Prediction capability from these seven variable toward ROA is 35,1% where the balance (64,9%) is affected to other factor which was not to be entered to research model.